COV-19 RELATED DISCOURSE GENERIC ANALYSES - Goradze, Tamta; Gvarishvili, Zeinab (International Journal of Innovative Technologies in Social Science, 2023)
COVID-19 related discourse has been gaining widespread attention due to its extension and coverage area (geographical area, age groups, layers of society, etc.). It can therefore be argued that the problem is global and sorting it out goes far of the local medical interventions. Cov-19 related discourse, presented by authoritative persons on the press conference (which is not a coincidental area and plays an intermediary role), responsible for preventing the society from killing virus requires not only medical treatment but the real art of communication as well.On the one hand, selecting an efficient communicative strategy and on the other, analyzing a real idea lying under meticulously chosen generic features requires generic analyses of either discourse or a text.This paper is established on corpus based linguistic analysis, which enabled us to identify the frequency and apportioning of each discourse marker observed in target empirical material, to highlight dominant and supplementary discourse features, to strengthen hypotheses that Cov-19 related discourse or a text is hybrid. Over and above that, analyses outcome, sheds new light on generic features of COVID-19 related discourse and opens a wider scope for a socio-critical look at what responsible persons do with language and why do they do it.